Pengaruh Dosis Injeksi Antemortem Papain Kasar terhadap Kualitas Fisik dan Organoleptik Daging Ayam Petelur Afkir pada Jenis Otot yang Berbeda - Agustin Widiastuti; Pudjomartatmo Pudjomartatmo; Adi Magna Patriadi Nuhriawangsa (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The research was aimed to observe the effect of antemortem injection dose of crude papain, muscle part and its interaction on physical and organoleptic qualities post production laying hen meat. The sample used were the breast and thighs from 20 hens on average age 82 weeks. Completely Randomized Design (CRD) used Factorial Pattern 4 x 2. Factor A consisted A1: without papain (control); A2: 1 mg papain/ kg BW; A3: 2 mg papain/ kg BW and A4: 3 mg papain/ kg BW, factor B consisted B1: breast muscle and B2: thigh muscle. The datas were analyzed by Analysis of Variance and continued by Duncan's Multiple Range Test. The results showed that injection of crude papain dose gave highly significant difference (P<0.01) to all variables except tensile strength (P<0.05). Body parts gave highly significant difference (P<0.01) on shear force, tensile strength, WHC, cooking loss, organoleptic (shear force, texture and juice), and hedonic (P<0.05). The interaction was found between injection of crude papain dose and body part on WHC, organoleptic and hedonic (P<0.01), cooking loss (P<0.05). Dose of 3 mg/kg WB in thigh and breast meat has the best quality and the organoleptic quality of the combination of papain injection of 3 mg/kg WB in breast meat and 2 mg/kg WB in thigh meat has the best quality.Keywords: antemortem injection, crude papain, physical and organoleptic quality, post productionlaying hen meat